2006
DOI: 10.1016/j.cryobiol.2006.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of Crassostrea gigas vesicular cells: Viability and metabolic activity

Abstract: Cryopreservation is widely used for long-term conservation of various tissues, embryos or gametes. However, few studies have described cryopreservation of invertebrate primary cell cultures and more particularly of marine invertebrate somatic cells. This technique would however be of great interest to facilitate the study of various metabolic processes which vary seasonally. The aim of the present study was to develop a protocol for cryopreservation of Crassostrea gigas vesicular cells. Different parameters we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 38 publications
1
10
0
1
Order By: Relevance
“…However DMSO has been shown to induce mutagenicity in the Ames test [30] so it was decided not to continue with DMSO for use in cryopreservation of haemocytes. Ethylene glycol has been used in cryopreservation of haemocytes of Haliotis tuberculata and vesicular cells of C. gigas [20,31]. It shows genotoxicity in the presence of S9 mix in CHO cells and it has been suggested that ethylene glycol can be metabolised by P450-dependent alcohol-dehydrogenases and form the reactive metabolite, glycoaldehyde, which would induce DNA-protein cross-linking [32,33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However DMSO has been shown to induce mutagenicity in the Ames test [30] so it was decided not to continue with DMSO for use in cryopreservation of haemocytes. Ethylene glycol has been used in cryopreservation of haemocytes of Haliotis tuberculata and vesicular cells of C. gigas [20,31]. It shows genotoxicity in the presence of S9 mix in CHO cells and it has been suggested that ethylene glycol can be metabolised by P450-dependent alcohol-dehydrogenases and form the reactive metabolite, glycoaldehyde, which would induce DNA-protein cross-linking [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Since intracellular ice formation can occur with supercooling and possible cell-membrane damage can result from eutectic crystallisation during the thawing process, a slow freezing rate and a rapid thawing rate have been proposed to maximise haemocyte survival and minimise haemocyte injury, especially DNA damage. Studies have shown optimal cooling rates for cells and tissues of marine organisms to vary between −1 • C and −5 • C min −1 , with rapid thawing at 37 • C [20,31]. To give a controlled cooling rate the CoolCell ® (BioCision LLC) system was used, which guarantees a cooling rate of −1 • C min −1 when stored at −80 • C. In addition, although the same cooling rate is not guaranteed, this system can actually be used in the vapour phase of a 'dry shipper' and is therefore suitable for fieldwork.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the final goals of our study is to obtain purified cell suspensions in order to develop homologous functional bioassays in oyster. At present, only haemocytes and storage cells of oysters can be maintained for a few days; these have been used, respectively, in immunological (Labreuche et al 2006;Lelong et al 2007) and energetic metabolism (Berthelin et al 2000;Kellner et al 2002;Hanquet-Dufour et al 2006) studies. Until recently, exploration of the functional role of molecules identified in oyster was only based on heterogeneous systems like rabbit chondrocytes to study the role of a chitinase (Badariotti et al 2006) or zebra fish embryos to explore the function of a receptor of the TGF-β family (Le Quéré et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The first attempts of cryopreservation of oocytes were made with mice in the 70's (Watson and Fuller, 2001) and nowadays great efforts have been made for the cryopreservation of human oocyte, where significant advances have been accomplished (Fabbri et al, 2001;Bianchi et al, 2005;Borini et al, 2006). Hence, if there has been little success in the cryopreservation of oocyte in mammals, less advances have been obtained with aquatic species (Hanquet-Dufour et al, 2006).…”
Section: Introductionmentioning
confidence: 99%